2022
DOI: 10.3390/ma15020442
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Design Methodology for Patient-Specific Short Femoral Stems

Abstract: The biomechanical performance of hip prostheses is often suboptimal, which leads to problems such as strain shielding, bone resorption and implant loosening, affecting the long-term viability of these implants for articular repair. Different studies have highlighted the interest of short stems for preserving bone stock and minimizing shielding, hence providing an alternative to conventional hip prostheses with long stems. Such short stems are especially valuable for younger patients, as they may require additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 77 publications
0
3
0
2
Order By: Relevance
“…La artroplastia total de cadera se considera uno de los procedimientos más exitosos en ortopedia durante las últimas décadas. Consiste en una intervención quirúrgica donde se hace un cambio total o parcial de la articulación de la cadera con un dispositivo artificial (prótesis) para restaurar el movimiento articular que puede dañarse debido a la fractura del cuello o cabeza femoral y a enfermedades como la osteoartritis, artritis reumatoide y osteonecrosis [5], [15]. Debido al desarrollo de la ingeniería mecánica asistida por ordenador y de las imágenes médicas, se empezó a realizar diseños a medida utilizando la TC del fémur para que la prótesis se adapte y fije al hueso naturalmente [5].…”
Section: Resultsunclassified
See 1 more Smart Citation
“…La artroplastia total de cadera se considera uno de los procedimientos más exitosos en ortopedia durante las últimas décadas. Consiste en una intervención quirúrgica donde se hace un cambio total o parcial de la articulación de la cadera con un dispositivo artificial (prótesis) para restaurar el movimiento articular que puede dañarse debido a la fractura del cuello o cabeza femoral y a enfermedades como la osteoartritis, artritis reumatoide y osteonecrosis [5], [15]. Debido al desarrollo de la ingeniería mecánica asistida por ordenador y de las imágenes médicas, se empezó a realizar diseños a medida utilizando la TC del fémur para que la prótesis se adapte y fije al hueso naturalmente [5].…”
Section: Resultsunclassified
“…Los vástagos femorales son un elemento crítico de la prótesis de cadera porque interactúan directamente con el hueso, y en el caso de los implantes sin cemento, su adherencia depende primordialmente de este elemento. Investigadores han propuesto el diseño personalizado de este componente basándose en la segmentación de la imagen médica, [5], [15], [19], [20]; seccionando transversalmente el modelo tridimensional del fémur y dibujando en cada corte el croquis del vástago con el suficiente contacto anatómico con las paredes internas del hueso para llenar la cavidad lo mejor posible, evitar la inestabilidad rotacional y favorecer el crecimiento óseo (Figura 5). Esta metodología es ineficiente porque el diseñador necesita obtener el modelo virtual, a partir de la TC, para ir sección a sección dibujando el implante, haciendo tediosa la personalización.…”
Section: Resultsunclassified
“…Stems C and D were shorter than the Taperloc® Complete stem and consequently induced a smaller amount of stress shielding in the implanted femur bone. Shortening the femoral stem length is a common way to reduce the amount of stress shielding induced in the implanted bone (Goshulak et al 2016;Solórzano-Requejo et al 2022). As the maximum initial micro-motion value for both stems B and C was smaller than 50 𝜇𝑚, and the maximum interface stress and stress shielding induced in the femur bone implanted by stem C was smaller than induced by stem B, stem C was selected as the shapeoptimized stem in this study.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the males exhibit a higher mean value of the resultant hip JRF than females at an elevation of 0°, 5°, 10° and 15° during single limb support and a significant effect was found on the mean value of the resultant of the hip JRF. A significant gender difference in gait patterns is demonstrated to occur while walking [ 23 ]. Comparable results were obtained by another study establishing that the the step length of females decreased compared to the step length of males during ramp walking.…”
Section: Discussionmentioning
confidence: 99%
“…An insight into these forces is a necessary requirement for designing of the hip joint prosthesis. In a total hip replacement arthroplasty a part of the femur including the head of the femur is removed and an artificial ball is secured to the thigh bone [ 23 ]. The artificial socket must articulate with the ball component and should be fixed in a position to maintain an optimal JRF and GRF at the hip joint ( Fig 9 ) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%